From China to Budapest: Experiences in attaining a BA in ELTE TÓK’s International Kindergarten Education Programme - Yimiao, Wang (Gyermeknevelés Tudományos Folyóirat, 2023)
From 2019 to 2022, I was glad to be a part of ELTE’s Faculty of Primary and Pre-School Education (ELTE TÓK) and study kindergarten education as an international student from China. It is a really lovely and beautiful school and I would like to provide some useful information about my experiences here. I hope this article can help those who are interested in the kindergarten education program offered by ELTE TÓK.